2000
DOI: 10.1007/pl00002320
|View full text |Cite
|
Sign up to set email alerts
|

Combined Fractionated External Beam Radiotherapy and Low-Dose-Rate Iodine-125 Seeds in an Experimental Tumor System

Abstract: The combined treatment of tumors with implanted low-dose-rate iodine seeds and external beam irradiation can decrease the total dose of the external beam irradiation and, hence, offer the possibility of considerable dose sparing of normal tissues without compromising local tumor control rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2001
2001
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
1
0
3
Order By: Relevance
“…In his analysis of long-time survivors, Gerhards et al [6] found 19% of the patients with and only 11% of the patients without postoperative external beam irradiation and brachytherapy among them. In combined external beam and brachytherapy irradiation, brachytherapy dose will reduce the necessary tumor control dose applied by external beam techniques, as shown by Würschmidt et al [20] for 125-iodine seed implants in an experimental animal model (R1H rhabdomyosarcoma in rats). The tolerable dose for irradiation of extrahepatic bile duct carcinoma was suggested by Regine & Mohiuddin [14] in 1996 to be 70 Gy (external plus intraluminal dose).…”
Section: Discussionmentioning
confidence: 99%
“…In his analysis of long-time survivors, Gerhards et al [6] found 19% of the patients with and only 11% of the patients without postoperative external beam irradiation and brachytherapy among them. In combined external beam and brachytherapy irradiation, brachytherapy dose will reduce the necessary tumor control dose applied by external beam techniques, as shown by Würschmidt et al [20] for 125-iodine seed implants in an experimental animal model (R1H rhabdomyosarcoma in rats). The tolerable dose for irradiation of extrahepatic bile duct carcinoma was suggested by Regine & Mohiuddin [14] in 1996 to be 70 Gy (external plus intraluminal dose).…”
Section: Discussionmentioning
confidence: 99%
“…Für die Therapie des lokal begrenzten Prostatakarzinoms stehen kurativ intendierte, klinisch etablierte Behandlungsoptionen [5] wie radikale Prostatektomie, perkutane oder interstitielle Strahlentherapie zur Verfügung [2,3]. Weiterhin gibt es experimentelle Verfahren wie die laparoskopische Prostatektomie, Bestrahlung mit schweren Teilchen [15] oder an einem experimentellen Tumorsystem eine kombinierte Therapie aus perkutaner Photonenbestrahlung und interstitieller Jod-125-Brachytherapie [17]. Die Zahl der Kliniken, die eine interstitielle Brachytherapie der Prostata mit Jod-125-Seeds anbieten, nimmt stetig zu.…”
Section: Hintergrundunclassified
“…Für die Behandlung des Prostatakarzinoms gibt es verschiedene etablierte kurative [6] und experimentelle Ansätze [18,25]. Das lokal begrenzte Prostatakarzinom kann durch interstitielle Brachytherapie mit Jod-125-Seeds erfolgreich therapiert werden [2,3,6,16,17,19].…”
Section: Hintergrundunclassified